Hyperglycaemia in acute coronary syndromes: risk-marker or therapeutic target?. Issue 9 (12th August 2008) - Anantharaman, R; Heatley, M; Weston, C F M
Abstract : Patients with acute coronary syndrome (ACS) often have raised blood glucose concentrations when admitted to hospital; a marker for poorer prognosis. Interventions to rapidly normalise blood glucose inconsistently are applied and with uncertain utility. Here we review the association of hyperglycaemia with outcome, present evidence that this hyperglycaemia reflects more than a pre-existing diabetic state and discuss mechanisms by which glucose may adversely affect the course of acute myocardial infarction (AMI). Finally, we seek evidence that intensive insulin treatment improves outcome.